Avaliação da restrição comercial na economia brasileira no período 1990-2009 à luz da lei de Thirlwall - Hybner, Bruno Reinoso (2010)
The aim of this dissertation is to undertake an assessment of the restriction of foreign trade performance in the Brazilian economy for the period 1990-2009, using as theoretical support Thirlwall's Law (1979). First, he made an experiment to test the validity of Thirlwall's Law for the Brazilian economy from 1990 to 2009 using the methodology proposed by McCombie (1997), which is to calculate an income elasticity of imports and hypothetical test it to see if it is the same as actually observed, where the acceptance of equality of these parameters is that growth is constrained by Brazil's trade balance, according to the theory in question. In this case, we used the technique of Johansen co-integration to obtain the results, which allowed validating Thirlwall's Law. Subsequently, a second experiment, we used the method of ordinary least squares to estimate the coefficients of the equations of demand for imports and exports for three periods, marked by economic events with different consequences for the adjustment of trade restriction in each. Thirlwall's Law in the first period, the trade restriction limited the average growth in Brazil 82% of the world average, in the intermediate, 35% and, at last, 86%. Finally, we proceeded to a qualitative analysis of the trade agenda according to the classification of industries by technological intensity. The data showed an increased participation of products with low added value and technological complexity, resourceintensive in exports, while imports were concentrated in goods with higher technology. This framework also allows the staff to place the commercial domestic growth constrained by the foreign trade performance. The results obtained by experiments in conjunction with the examination of the trade agenda by technological intensity this dissertation leads to the intuition that the restriction of foreign trade performance may be considered one of the explanations for the average growth rate of Brazil in the interval in question have remained below the global average.